2018
DOI: 10.48550/arxiv.1811.00507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Localised necessary conditions for singularity formation in the Navier-Stokes equations with curved boundary

Abstract: We prove two results concerning local regularity theory of the Navier-Stokes equations near a curved portion Γ ⊂ ∂ Ω of the boundary. Suppose that u is a boundary suitable weak solution with singularity (x * , T * ), where x * ∈ Ω ∪ Γ. Then (under a weak background assumption) the L 3 norm of u tends to infinity in every ball centered at x * :Furthermore, u gives rise to a non-trivial mild bounded ancient solution in R 3 or R 3 + through a rescaling procedure that zooms in on the singularity. This generalizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This result has been further refined to other wider critical spaces and to domains other than R 3 . See, for example, [2], [3]- [4], [8] and [28]. All these arguments are qualitative and achieved by contradiction and compactness arguments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result has been further refined to other wider critical spaces and to domains other than R 3 . See, for example, [2], [3]- [4], [8] and [28]. All these arguments are qualitative and achieved by contradiction and compactness arguments.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of these quantitative estimates, Tao 3 We say (X, • X ) ⊂ S (R 3 ) is critical if u0 ∈ X ⇒ u 0λ (x) := λu(λx) ∈ X with X norm equal to that of u0. 4 The argument in [5] is in turn taken from the talk given by G . Seregin.…”
Section: Introductionmentioning
confidence: 99%
“…In [11], Constantin and Fefferman provided a geometric regularity criteria for the vorticity ω = ∇ × u of solutions on the whole-space, which remarkably does not depend on scale-invariant quantities. 1 Specifically, they showed that if 2 (2) | sin(∠(ω(x + y, t), ω(x, t))| ≤ C|y| for (x, t) ∈ Ω d := {(y, s) ∈ R 3 × (0, T ) : |Ω(y, s)| > d} Date: June 20, 2019. 1 By scale-invariant quantities, we mean quantities which are invariant with respect to the Navier-Stokes rescaling (u λ (y, s), p λ (y, s)) = (λu(λy, λ 2 s), λ 2 p(λy, λ 2 s)).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of regularity criteria for the Navier-Stokes equations are stated in terms of scale-invariant quantities since, heuristically at least, the diffusive effects and non-linear effects are 'balanced'. 2 Here ∠(a, b) denotes the angle between the vectors a and b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation